Microsatellite instability in endometrial cancer: the role of diagnostic methods and their clinical application. Expert consensus - A. S. Tyulyandina; E. A. Ulrikh; L. A. Kolomiets; S. E. Krasilnikov; A. G. Kedrova; A. A. Rumyantsev; G. A. Raskin; A. I. Nesterova; M. V. Volkonskiy; O. N. Churuksaeva; A. Yu. Goryainova; V. V. Zhavoronkova; et al. (ABV-press, 2023)
Deficient DNA mismatch repair (dMMR) is a rare molecular disorder found in 20-30 % of endometrial tumors. Laboratory identification of dMMR/microsatellite instability (MSI) has a high diagnostic value, since these impairments are considered as biomarkers of endometrial adenocarcinoma. They help to identify patients at high risk of Lynch syndrome, evaluate the disease prognosis, and estimate the efficacy of immune checkpoint inhibitors and their combinations. This review details current concepts of MSI diagnostics and discusses its predictive value in patients with endometrial cancer. It also describes a new diagnostic algorithm for the detection of dMMR and MSI.